ECG Quiz 41 Answer - Chin, Ashle; Millar, Rob Scott (SA Heart Journal, 2017)
The ECG shows a wide complex, regular QRS tachycardia. The rate of the tachycardia is 264bpm. The QRS complexes are wide (140ms). The QRS axis of the tachycardia is +90 degrees. There is positive concordance in the chest leads.